Pengembangan Model Penentuan Lokasi Astrowisata di Indonesia Menggunakan Metode Analytic Hierarchy Process (AHP): Studi Kasus Danau Ranau - Prastyo, Hendra Agus; Hafizah, Izatul; Rozzykin, Achmad Zainur; Esthi, Surya Tri (Jurnal Ilmiah Pariwisata, 2026)
Astrotourism is a form of ecotourism that utilizes the quality and beauty of the night sky as its main attraction. The development of astrotourism in Indonesia requires an integrated approach that considers astronomical, meteorological, and tourism aspects. This study aims to develop a site selection model for astrotourism called Holistic Astrotourism Potential (HAP) which is built using the Analytic Hierarchy Process (AHP) method and to implement it in the Danau Ranau area as a case study. A total of 13 parameters were employed, including night sky brightness, observation field of view, cloud cover, thermal comfort, accessibility, and tourism facilities. Parameter weights were determined based on expert judgments from astronomy, meteorology, and tourism fields. The proposed model was applied to six sampling locations around Danau Ranau using field observations, astronomical measurements, and meteorological data. The results indicate that Pantai Bidadari has the highest astrotourism potential among the evaluated sites, supported by favorable night sky quality and clear visibility of the Milky Way. The developed model is expected to serve as a reference for sustainable astrotourism planning and development in Indonesia. Keywords: analytic hierarchy process, astronomy, astrotourism, Danau Ranau, meteorology, tourism